Modifiable risk factors associated with the risk of developing Parkinson's disease: a critical review - Tumas, Vitor; Aureliano, Marcelo Jhonatan; Rieder, Carlos Roberto de Melo; Schuh, Artur Francisco Schumacher; Ferraz, Henrique Ballalai; Borges, Vanderci; Soares, Maria Carolina; Boone, Dayany Leonel; Silva, Carolina Candeias da; Costa, Mariana Cavalcanti; Silva, Delson José da; Carmo, Aracelle Victor do; Mikael, Luana de Rezende; Santos-Lobato, Bruno Lopes; Rosso, Ana Lucia Zuma; Vilaça, Celmir de Oliveira; Braga-Neto, Pedro; Gomes, André Borges Ferreira; Carvalho, Camila Gonçalves Monteiro; Letro, Grace Helena; Nicaretta, Denise Hack; Coletta, Marcus Vinicius Della; Barbosa, Egberto Reis; Cury, Rubens Gisbert; Cardoso, Francisco Eduardo Costa; Camargos, Sarah Teixeira; Mata, Ignacio Fernandez (Arquivos de Neuro-Psiquiatria, 2025)
The etiology of Parkinson's disease (PD) is complex and multifactorial, depending on interactions involving environmental/lifestyle and genetic factors. The genetic aspects of the disease are becoming well characterized, while the environmental factors still need further investigation. In the present narrative review, we have described the most concrete evidence of associations between environmental factors and the risk of developing PD. Physical activity, healthy dietary patterns, smoking, and caffeine intake are protective factors against PD. Head trauma, consumption of milk and dairy products, and pesticide exposure were associated with a higher risk of developing PD. The associations of alcohol consumption, living in rural areas, farming, and consumption of well water with PD are still controversial. Results of several studies strongly suggest that diabetes mellitus is a risk factor for the development of PD, as well as the pre-diabetic state. Lower serum levels of uric acid were associated with an increased risk of developing PD and with worse clinical features and faster progression of symptoms. The protective effects of nonsteroidal antiinflammatory drugs use are controversial. Several other factors were potentially associated with the risk of developing PD: environmental pollutants such as organic solvents, exposure to sunlight, vitamin D deficiency, bullous pemphigoid, bipolar disorder, inflammatory bowel disease, irritable bowel syndrome, certain infections and agents, and essential tremor. Environmental factors are important risk markers for the development of PD. Understanding these risks and protective factors could lead to the implementation of risk-modifying actions for PD.
Keywords: Parkinson Disease; Risk Factors; Etiology; Protective Factors; Environmental Exposure